Learning to read in Chinese: Evidence for reciprocal relationships between word reading and oral language skills. Issue 1 (2nd October 2018) - Hulme, Charles; Zhou, Lulin; Tong, Xiuli; Lervåg, Arne; Burgoyne, Kelly
Abstract: This study investigates the longitudinal predictors of the development of Chinese word reading skills and potential bidirectional relationships between Chinese word reading and oral language skills. We examine, in a 2‐year longitudinal study, a wide range of theoretically important predictors (phonological awareness, tone awareness, morphological awareness, visual skills, rapid automatized naming, Pinyin knowledge, and vocabulary knowledge) of reading in 143 primary‐school children living in mainland China. Initial levels of reading were predicted by vocabulary knowledge, phonological awareness, and visual discrimination skills. Only initial reading levels predicted growth in reading. Initial reading also predicted growth in vocabulary knowledge and morphological construction. This pattern demonstrates that the early stages of learning to read in Chinese places demands on semantic (vocabulary) and visual skills in addition to phonological skills. Furthermore, early levels of word reading predict the growth of vocabulary knowledge and morphological awareness suggesting that the development of these oral language skills is facilitated by learning to read. Abstract : Early Chinese word reading skills were predicted by vocabulary, phonological awareness and visual discrimination in a large sample of 7 year old children. This study also demonstrates that learning to read in Chinese has reciprocal effects on oral language (vocabulary and morphological awareness).